Return of the Lemnaceae: duckweed as a model plant system in the genomics and postgenomics era. Issue 10 (17th July 2021) - Acosta, Kenneth; Appenroth, Klaus J; Borisjuk, Ljudmilla; Edelman, Marvin; Heinig, Uwe; Jansen, Marcel A K; Oyama, Tokitaka; Pasaribu, Buntora; Schubert, Ingo; Sorrels, Shawn; Sree, K Sowjanya; Xu, Shuqing; et al.
Abstract: The aquatic Lemnaceae family, commonly called duckweed, comprises some of the smallest and fastest growing angiosperms known on Earth. Their tiny size, rapid growth by clonal propagation, and facile uptake of labeled compounds from the media were attractive features that made them a well-known model for plant biology from 1950 to 1990. Interest in duckweed has steadily regained momentum over the past decade, driven in part by the growing need to identify alternative plants from traditional agricultural crops that can help tackle urgent societal challenges, such as climate change and rapid population expansion. Propelled by rapid advances in genomic technologies, recent studies with duckweed again highlight the potential of these small plants to enable discoveries in diverse fields from ecology to chronobiology. Building on established community resources, duckweed is reemerging as a platform to study plant processes at the systems level and to translate knowledge gained for field deployment to address some of society's pressing needs. This review details the anatomy, development, physiology, and molecular characteristics of the Lemnaceae to introduce them to the broader plant research community. We highlight recent research enabled by Lemnaceae to demonstrate how these plants can be used for quantitative studies of complex processes and for revealing potentially novel strategies in plant defense and genome maintenance. Abstract : The characteristics of the Lemnaceae are introduced to the plant biology community, and recent studies are described showing how duckweed represents an ideal model for systems-level investigations.